Air Pollution Monitoring, Quantification and Removal of Gases and Particles - Del Real Olvera, Jorge (IntechOpen, 2019)
Currently, one of the most evident and dangerous contaminants aspects for the health of all living beings is air pollution. To understand the severity of this environmental problem, in this book the authors make an in-depth review of different environmental aspects on monitoring, quantification and elimination of emissions to the atmosphere, generated by diverse anthropogenic activities in large cities. Contributors of this book have made an effort to put their ideas in simple terms without forgoing quality. The principal objective of this book is to present the most recent technical literature to all interested readers in this field.